Teacher Reflection on a Teaching-Learning Situation Regarding the Concept of Relation in Secondary Education - PICADO, MIGUEL (2022)
This study is part of the research in didactics of mathematicson teacher training. In particular, the study focuses on the knowledge of mathematics teachers, taking as a reference the theoretical approaches of the Mathematics Teacher’s Specialized Knowledge (MTSK) model and teacher reflection as a professional competence. The study corresponds to a descriptive-qualitative research, based on an instrumental study of cases, whose purpose is to describe and analyze the manifestations of mathematics teachers of Secondary Education when they observe a teaching-learning situation that shows a teacher of mathematics teaching the concept of relation. For this, narratives written by seven Secondary Education mathematics teachers in service were used, which indicate some aspects identified by them as relevant from the observed situation. The analysis of the gathered information was carried out by defining categories, subcategories, and analysis units based on the components of the MTSK model. The results indicate that participating teachers accentuate, in their manifestations, attributes mainly associated with didactic knowledge of mathematical content. The reflection of this group of teachers is characterized by three specific aspects of the MTSK model: teaching, learning, and knowledge of the topics. It is interpreted that teacher reflection has been influenced by the professional experience of the teachers participating in the study.